THE PERCEPTION OF EDUCATOR ACCOUNTANTS & ACCOUNTING DEPARTMENT STUDENTS TOWARDS THE IKATAN AKUNTAN INDONESIA’S CODE OF ETHICS - Pratiwi, Tamara Syva B1034161017 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2020)
ABSTRACT     This study aims to understand the perceptions of accountants educators in the field of accounting and perceptions of accounting department students as academics towards the IAI?s code of ethics. The analysis is given to the answers of respondents obtained through a questionnaire published in the city of Pontianak.     This study uses primary data obtained by questionnaire to the selected respondents. Respondent criteria for educator accountants are accountants as educators in the city of Pontianak and are members of the Indonesian Institute of Accountants (IAI). Meanwhile, criteria for accounting department students are students that still listed as an undergraduate accounting student who has taken or is currently taking courses in Auditing and Professional Ethics courses.     The study began with testing the validity and reliability of the list of questions used in the questionnaire. To test the validity of using Pearson correlation while testing the reliability using the Cronbach Alpha (a) method. The next analysis is the requirements of the hypothesis test tool requirements. Variants Test the distribution of normality and homogeneity tests. The normality test of data distribution in this study uses the Statistical Package Method for Social Sciences (SPSS) Kolmogorov-Smirnov Test and the data homogeneity test in this study uses the Statistical Package Method for Social Sciences (SPSS) Homogenity of Variances Test.     The research hypothesis testing was carried out using a statistical analysis tool namely the Independent Sample T-Test using the help of the SPSS 25 program (Statistical Package for Social Sciences). The results of the study showed that there were differences between accounting department students and accountant educators on the IAI?s Code of Ethics.     Keywords: Perception, code of ethics of accountants, accountants educators, accounting department students. REFERENCESAgoes, S. (2004). Auditing (Pemeriksaaan Akuntan) Oleh Kantor Akuntan Publik. Jakarta: Fakultas Ekonomi Universitas Indonesia.Al, H. J. (2001). Dasar-Dasar Akuntansi Jilid 2. Yogyakarta: Sekolah Tinggi Ilmu YKPN.Ariesetyawan, R. (2010). ANALISIS PERSEPSI AKUNTAN PUBLIK DAN MAHASISWA PENDIDIKAN PROFESI AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA.Ariesetyo M, O. (2007). PERBEDAAN PERSEPSI AKUNTAN PENDIDIK DAN MAHASISWA PRODI AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA.Brooks. (2007). Medical Microbiology. USA.Depdikbud. (1995). Kamus Besar Bahasa Indonesia. Jakarta: Balai Pustaka.Diamastuti, E. (2014). Dilema Etika dan Simbolisme Kode Etik Akuntan Manajemen Perspektif Kualitatif-Fenomenologis (Studi Pada Sebuah BUMN Di Indonesia).Gibson. (1996). Organisasi, Perilaku, Struktur, Proses. Jakarta: Bina Rupa Aksara.Handayani, Z. (2013). PERBEDAAN PERSEPSI AUDITOR, AKUNTAN PENDIDIK DAN MAHASISWA JURUSAN AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA.Husein, U. (1997). Studi Kelayakan Bisnis.Husein, U. (2003). Metodologi Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Gramedia Pustaka.Ikatan Akuntan Indonesia. (1975). Kode Etik Akuntan Indonesia. Jakarta : IAI.Ikatan Akuntan Indonesia. (2001). Kompartemen Akuntan Publik - Standar Profesional Akuntan Publik. Jakarta: Salemba Empat.Jhuhara, D. (2017). PENGARUH KODE ETIK AKUNTAN PUBLIK TERHADAP KUALITAS HASIL AUDIT PADA KANTOR AKUNTAN PUBLIK DI BANDUNG.Lubis, S. K. (1994). Etika Profesi Hukum. Jakarta: Sinar Grafika.Ludigdo, U., & M, M. (1999). Persepsi Akuntan dan Mahasiswa tentang Etika Bisnis. Jurnal Riset Akuntansi Indonesia , Vol.2, No.1 Hal. 1-19.Maryani T, & Unti, L. (2001). Survei Atas Faktor-Faktor yang Mempengaruhi Sikap dan Periaku Etis Akuntan.Novatiani, R. (n.d.). Analisis Penerapan Kode Etik Profesi pada Kantor Akuntan Publik (KAP) Di Kota Bandung. Jurnal Ekonomi Intensif.Nuraina, E., & Kurniawati, S. H. (2012). PERBEDAAN PERSEPSI AKUNTAN PENDIDIK DAN MAHASISWA PRODI AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA. Jurnal Dinamika Akuntansi, 111-120.Nurlan, A. B. (2011). PERSEPSI AKUNTAN DAN MAHASISWA JURUSAN AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA.Oerip, & Tatag, U. (2000). Mengatasi Krisis Manusia di Perusahaan. Jakarta: Grasindo.Rahayu, S. K. (2010). PERPAJAKAN INDONESIA: Konsep dan Aspek Formal. Yogyakarta: Graha Ilmu.Regar, M. (2003). Kilas Sorot Perkembangan Akuntansi di Indonesia. Jakarta: Pustaka LP3ES.Robbins, S. P. (2009). Perilaku Organisasi. Jakarta: Salemba Empat.Rusmayanto. (2014). PERSEPSI MAHASISWA AKUNTANSI TERHADAP KODE ETIK AKUNTAN.Salam, B. (1996). Etika Sosial. Rinerka Cipta.Sartika, D. (2006). Persepsi Dosen Akuntansi Dan Mahasiswa Akuntansi. Skripsi Sarjana Fakultas Ekonomi Jurusan Akuntansi Universitas Bengkulu.Sihwahjoeni, & M, G. (2000). Persepsi Akuntan terhadap Kode Etik Akuntan. Jurnal Riset Akuntansi Indonesia.Simamora, H. (2002). Auditing I. Yogyakarta: UPP AMP YKPN.Singarimbun, & Sofyan, E. (1995). Metode Penelitian Survei. Jakarta: LP3ES.Sugiyono. (1997). Metodologi Penelitian Bisnis. Bandung: CV Alfabeta.Sugiyono. (2003). Metode Penelitian Bisnis. Bandung: Alfabeta.Sunarto. (2003). "Auditing". Pena Persada.Universitas Tanjungpura, F. (2017). Pedoman Penulisan Karya Akhir.Wati, R. Y. (2016). Persepsi Mahasiswa Akuntansi Terhadap Etika Profesi Akuntan (Studi pada PTN dan PTS di Jember).Wibowo, S. A. (2006). PERSEPSI MAHASISWA AKUNTANSI DAN AKUNTAN PENDIDIK TERHADAP KODE ETIK AKUNTAN.Widyawati, & S, A. I. (2010). PERBEDAAN PERSEPSI AKUNTAN PUBLIK, AKUNTAN PENDIDIK, DAN MAHASISWA AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA.Wulansari, A. (2008). Studi Persepsi Mahasiswa Akuntansi terhadap Profesionalisme Dosen Akuntansi Perguruan Tinggi.Yulistiana, R. (2015). Persepsi Mahasiswa Akuntansi Terhadap Etika Profesi Akuntan (Studi pada PTN. Artikel Ilmiah Mahasiswa.Yusriani. (2005). Persepsi Akuntan Pendidik dan kuntan Publik Terhadap Kode Etik Akuntan Indonesia. Semarang.